Implemented Project Based Learning on Japanese Writing Skills - Makhsusy Permatasari, Kun; Agustine, Irawati (International Journal of Educational Research & Social Sciences, 2023)
The purpose of this study is to determine the effectiveness of project-based learning on Japanese writing skills. The study employs a quasi-experimental design. This study was carried out at a private university in Jakarta during the odd semester of 2023-2024. Participants included 50 students from a Japanese writing class. As a result, the data is derived from observations, documents, and tests. The t-test is used in the data analysis technique: Two-Pair Sample for the Mean. According to the findings of the study, project-based learning improved Japanese writing skills. Students have received enough training to actively write Japanese both individually and in groups. As a result, project-based learning is quite effective and can continue to be developed with learning media.